A perceived reliability-based customer satisfaction model in self-service technology. Issue 7 (11th June 2018) - Barua, Zapan; Aimin, Wang; Hongyi, Xu
ABSTRACT: Technical reliability of self-service technologies (SSTs) has been found to be a strong determinant of satisfaction with tech-enabled services. Yet, the interpretation of the factors affecting reliability and its subsequent influences on customer satisfaction (CS) with SSTs is inadequate. The purpose of this investigation has, therefore, been to demarcate a model to fulfill the gap with an empirical examination, and accordingly a model was developed and tested by applying a global structural equation model. The model results of banking SST users specify how the reliability of SSTs is perceived by the users. The findings have reported that the best predictor of perceived reliability (PRe) is perceived security followed by perceived control. Surprisingly, no significant impact of perceived ease of use was found on PRe. The research also attempted to shed light on the influence of PRe on perceived risk, technology trust, and CS in the light of technology-enabled self-service.